Discretized current distribution for active endcap transverse gradient coil design for magnetic resonance imaging using stream function approach (Journal of Bangladesh Academy of Sciences, 2011)
The authors present the discretized form of the current distribution using the stream function approach starting from a continuous current distribution obtained recently for an active endcap transverse gradient coil in Magnetic Resonance Imaging (MRI) machine. The present discretized current distribution is compared with the one found using apodized current distributions on the cylinder and the cap surfaces separately and its advantages are discussed. Key words: Gradient coils; Stream function; Active endcap DOI: 10.3329/jbas.v34i2.6858Journal of Bangladesh Academy of Sciences, Vol. 34, No. 2, 143-152, 2010